2014
DOI: 10.1016/j.actamat.2014.08.038
|View full text |Cite
|
Sign up to set email alerts
|

The role of abnormal grain growth on solid-state dewetting kinetics

Abstract: Continuous thin films of Pt on A-plane 1 1 2 0 À Á sapphire substrates were dewetted to characterize the morphological evolution and dewetting kinetics at 800°C using an oxygen partial pressure of 10 À20 atm. Hole growth was studied, focusing on partially dewetted samples. Four different low-index orientation relationships were found between the Pt and sapphire substrate by electron backscattered diffraction combined with transmission electron diffraction patterns. Abnormal grains adjacent to the holes with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…Similar observations have been made by Tesler et al [51] on discontinuous Au films interpreting it as the onset of abnormal grain growth. The importance of grain growth prior to dewetting has also been remarked by Luber et al [50] studying Ni thin films on SiO 2 and in a recent work, Atiya et al [66] found the dewetting of Pt thin films on sapphire even to be dominated by abnormal grain growth. The initial transformation cannot be further discussed on the basis of the performed experiments, as it is temporally not resolved and occurs during the heating ramp.…”
Section: General Observationsmentioning
confidence: 85%
“…Similar observations have been made by Tesler et al [51] on discontinuous Au films interpreting it as the onset of abnormal grain growth. The importance of grain growth prior to dewetting has also been remarked by Luber et al [50] studying Ni thin films on SiO 2 and in a recent work, Atiya et al [66] found the dewetting of Pt thin films on sapphire even to be dominated by abnormal grain growth. The initial transformation cannot be further discussed on the basis of the performed experiments, as it is temporally not resolved and occurs during the heating ramp.…”
Section: General Observationsmentioning
confidence: 85%
“…Tesler et al [32] observed a dependence on the initial film thickness of Au thin films dewetting on glass substrates. Most recently Atiya et al [35] have elucidated the role of abnormal grain growth during dewetting of Pt thin films on a sapphire substrate. They observed abnormal grain growth of preferentially oriented grains, as soon as they are in contact with the retracting edge of a growing void.…”
Section: Introductionmentioning
confidence: 99%
“…Due to confinement at the surface of the substrate, both diffusion on the free surface of the film and at the interface with the substrate can participate in the process. Mechanisms and kinetics of dewetting depend on the nature of both film and substrate (crystalline or amorphous) as well as on the annealing atmosphere; they have been studied in particular for films of the platinum group and of noble metals . Yet, in the case of complex polycrystalline films on amorphous flat substrates, recent studies using various in situ and real‐time measurement imaging techniques have shed light on the major role played by grains in the kinetics of dewetting and in the evolution of the coverage/density of objects and holes .…”
Section: Introductionmentioning
confidence: 99%